Re-spatialization of time series plots. (October 2017) - Abdul-Rahman, Alfie; Walton, Simon; Bemis, Karen; Lein, Julie Gonnering; Coles, Katharine; Silver, Deborah; Chen, Min
Visualizing time series is a ubiquitous aspect of many applications from science to business. The conventional designs of line graphs and temporal parallel coordinates plots focus on the depiction of the temporal context, but typically fail to convey the spatial information associated with data values at each time step. In this paper, we present a study of the design space for reintroducing spatial context to time series plots. We consider a range of options, from color encoding to glyph encoding, from abstract illustration to realistic representation, and from interactive brushing to animated three-dimensional viewing. We evaluate these design options in conjunction with two case studies: (i) observing events in temporal sensory data of seafloor hydrothermal plumes and (ii) observing phonemic dynamics in poems. We report domain experts' comparative assessment, which provides an insight into the effectiveness of different re-spatialization methods.